2014
DOI: 10.1212/wnl.0000000000000125
|View full text |Cite
|
Sign up to set email alerts
|

Safety and efficacy of ofatumumab in relapsing-remitting multiple sclerosis

Abstract: This study provides Class II evidence that in patients with RRMS, ofatumumab compared with placebo does not increase the number of serious adverse events and decreases the number of new MRI lesions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
221
0
3

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 265 publications
(234 citation statements)
references
References 30 publications
4
221
0
3
Order By: Relevance
“…Heterogeneity existed among the included studies (I 2 =48%, P=0.68). Serious adverse events were reported in five studies (11)(12)(13)(14). As above, the overall results of the meta-analysis revealed that patients receiving anti-B-cell mAbs exhibited no significant difference in serious adverse events compared with those in the placebo group (OR=1.13; 95% CI= 0.70-1.80; P= 0.62; Fig.…”
Section: Volume Change Of Lesions From Baseline On T2-weighted Mrimentioning
confidence: 69%
See 4 more Smart Citations
“…Heterogeneity existed among the included studies (I 2 =48%, P=0.68). Serious adverse events were reported in five studies (11)(12)(13)(14). As above, the overall results of the meta-analysis revealed that patients receiving anti-B-cell mAbs exhibited no significant difference in serious adverse events compared with those in the placebo group (OR=1.13; 95% CI= 0.70-1.80; P= 0.62; Fig.…”
Section: Volume Change Of Lesions From Baseline On T2-weighted Mrimentioning
confidence: 69%
“…After reviewing the full text of the remaining 11 studies, four studies, including five trials (one study was regarded separately as two trials due to different dosages) with a total of 745 patients contained sufficient information to be included in the statistical analysis, and compared anti-B-cell mAbs with a placebo (11)(12)(13)(14). The most common reasons for exclusion were that studies were reviews, contained patients not diagnosed with MS, non-randomized clinical trials, use of a mAb other than rituximab, ocrelizumab or ofatumumab as a treatment intervention, and insufficient data (Fig.…”
Section: Study Characteristicsmentioning
confidence: 99%
See 3 more Smart Citations